2016
DOI: 10.1002/acp.3291
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Recollection Rejection in the Misinformation Paradigm

Abstract: The purpose of this research was to determine the role of recollection rejection in the rejection of misinformation. In Experiment 1, we examined the use of recollection rejection to reject contradictory and additive misinformation. We measured recollection rejection by comparing misinformation acceptance rates, graphing confidence-accuracy data using phantom receiver operating characteristic curves, examining high confidence rejections of misinformation, and examining self-report responses. These measures con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 46 publications
6
30
0
Order By: Relevance
“…In adults, recollection-based rejection strategies have been studied in eyewitness suggestibility paradigms (Loftus, 1979;Moore & Lampinen, 2016;Pezdek, Finger, & Hodge, 1997;Tousignant, Hall, & Loftus, 1986). For instance, Moore and Lampinen (2016) found that adults use recollection rejection to reject misinformation. These findings suggest the possibility that children may also use these strategies to reject suggested information about a witnessed event.…”
Section: Memory Editing In Childhoodmentioning
confidence: 99%
“…In adults, recollection-based rejection strategies have been studied in eyewitness suggestibility paradigms (Loftus, 1979;Moore & Lampinen, 2016;Pezdek, Finger, & Hodge, 1997;Tousignant, Hall, & Loftus, 1986). For instance, Moore and Lampinen (2016) found that adults use recollection rejection to reject misinformation. These findings suggest the possibility that children may also use these strategies to reject suggested information about a witnessed event.…”
Section: Memory Editing In Childhoodmentioning
confidence: 99%
“…Prior research has examined qualitative characteristics of misleading content that can influence subsequent suggestibility, such as how central versus peripheral the misleading details are to the original event (Luna & Migueles, ; Wilford, Chan, & Tuhn, ; Wright & Stroud, ). Here, we also examine qualitative characteristics of misleading items by contrasting two types of misinformation that have been studied less frequently (Frost, ; Huff & Umanath, ; Moore & Lampinen, ; Nemeth & Belli, ): contradictory and additive. Contradictory misinformation refers to suggested misleading details that are discrepant with specific details that were originally presented (e.g., the stop/yield sign discrepancy in the classic misinformation paradigm).…”
Section: Introductionmentioning
confidence: 99%
“…Until recently (Huff & Umanath, ; Moore & Lampinen, ), differences between contradictory and additive misinformation had not been systematically compared despite both types producing large misinformation effects (Frost, ; Nemeth & Belli, ; Saunders & Jess, ). Huff and Umanath () presented younger and older adults with a fictional story followed by misleading questions that contained additive and contradictory details that were systematically counterbalanced across misinformation type and participants.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations